Rencana Bisnis “Indonesian’s Coffee Shop” - Aloysius Derry (Universitas Tarumanagara, 2021)
This project was carried out to test the feasibility of a coffee shop business plan that was planned be built in Jakarta, Indonesia. Coffee has been a part of the lifestyle of Indonesian people for a long time. The relationship between coffee and lifestyle in Indonesia is the main reason that supports this project. This business plan is carried out by mapping the business model of the coffee shop. The business model of coffee shop is also analyzed by analyzing markets, market segments, Porter’s Five Forces analysis, PEST analysis, and SWOT analysis. The results of the analysis of the Indonesian’s coffee shop business model is have the best quality, affordable prices, and strategic location. The disadvantage requested is that as a new brand, it takes effort that can be well received by consumers. This weakness is a limitation of Indonesia's coffee shop to focus on supporting the development of information technology to support brand acceleration in order to support engagement with potential customers. Projection of income statement, net present value, and payback period. Quantitative test results indicate a business plan that is feasible to implement because it meets all eligibility criteria. Proyek ini dilakukan untuk menguji kelayakan rencana bisnis kedai kopi yang direncanakan akan dibangun di Jakarta, Indonesia. Kopi telah menjadi bagian dari gaya hidup masyarakat Indonesia sejak lama. Hubungan antara kopi dan gaya hidup di Indonesia adalah alasan utama yang mendukung proyek ini. Rencana bisnis ini dilakukan dengan memetakan model bisnis kedai kopi. Model bisnis kedai kopi juga dianalisa dengan menganalisis pasar, segmen pasar, analisa Porter’s five forces analisis PEST, dan analisis SWOT. Hasil analisis model bisnis Indonesian’s Coffee Shop adalah memiliki kualitas terbaik, harga terjangkau, dan lokasi yang strategis. Kerugian yang diminta adalah bahwa sebagai merek baru, dibutuhkan upaya yang dapat diterima dengan baik oleh konsumen. Kelemahan ini adalah keterbatasan Indonesian’s Coffee Shop untuk fokus mendukung pengembangan teknologi informasi untuk mendukung percepatan merek dalam rangka mendukung keterlibatan dengan pelanggan potensial. Proyeksi laporan laba rugi, Net Present Value, dan Payback Period. Hasil tes kuantitatif menunjukkan rencana bisnis yang layak untuk dilaksanakan karena memenuhi semua kriteria kelayakan.